Comparison of uranium(VI) and thorium(IV) coordination polymers with p-toluenesulfonic acid. (8th May 2015) - Zhang, Yingjie; Price, Jason R.; Karatchevtseva, Inna; Lu, Kim; Yoon, Bongho; Kadi, Fatima; Lumpkin, Gregory R.; Li, Feng
Graphical abstract: Uranium(VI) and thorium(IV) coordination polymers (CPs) with p -toluenesulfonic acid (PTSA) have been synthesized and characterized. Both CPs have one-dimensional (1D) structures and exhibit similar thermal stabilities. Vibrational modes have been investigated. Abstract: The reaction of uranium(VI) or thorium(IV) nitrate with p -toluenesulfonic acid (PTSA) in aqueous solutions at room temperature led to the formation of U(VI)/Th(IV) coordination polymers (CPs) with deprotonated μ 2 -bridging PTS anions. Both [(UO2 )(PTS)2 (PTSA)]·4H2 O (1 ) and Th(PTS)4 (H2 O)3 (2 ) have one-dimensional (1D) undulating polymeric structures built with pentagonal bipyramidal uranyl polyhedrons and 9-fold coordinated thorium polyhedrons, respectively, linked through μ 2 -bridging PTS anions. Both CPs have similar thermal decomposition patterns as they have similar structural type in the presence of the same ligand. Vibrational modes have been investigated and the structural features have been discussed together with relevant structures.